Outcomes of Intramedullary Nailing and External Fixation of Open Tibial Fractures: Three to Five-Year Follow-up of a Randomized Clinical Trial. (2nd November 2022) - Cortez, Abigail; Urva, Mayur; Haonga, Billy; Donnelley, Claire A.; von Kaeppler, Ericka P.; Roberts, Heather J.; Shearer, David W.; Morshed, Saam
Abstract : Background: While surgeons in low and middle-income countries have increasing experience with intramedullary nailing (IMN), external fixation (EF) continues to be commonly used for the management of open tibial fractures. We examined outcomes with extended follow-up of the participants enrolled in a clinical trial comparing these treatments. Methods: Adults who were ≥18 years old with acute AO/OTA type-42 open tibial shaft fractures were randomly assigned to statically locked, hand-reamed IMN or uniplanar EF. These participants were reevaluated 3 to 5 years after treatment. The primary outcome was death or reoperation for the treatment of deep infection, nonunion, or malalignment. Unresolved complications such as persistent fracture-related infection, nonunion, or malalignment were collected and analyzed. Secondary outcomes included the EuroQol-5 Dimension-3 Level (EQ-5D-3L) questionnaire, the Function IndeX for Trauma (FIX-IT) score, radiographic alignment, and the modified Radiographic Union Scale for Tibial fractures (mRUST). Results: Of the originally enrolled 240 participants, 126 (67 managed with IMN and 59 managed with EF) died or returned for follow-up at a mean of 4.0 years (range, 2.9 to 5.2 years). Thirty-two composite primary events occurred, with rates of 23.9% and 27.1% in the IMN and EF groups, respectively. Six of these events (3 in the IMN group and 3 in the EF group) were newly detected after the original 1-year follow-up. Unresolved complications in the form of chronic fracture-related infection or nonunion were present at long-term follow-up in 25% of the participants who sustained a primary event. The EQ-5D-3L index scores were similar between the 2 groups and only returned to preinjury levels after 1 year among patients without complications or those whose complications resolved. Conclusions: This observational study extended follow-up for a clinical trial assessing IMN versus EF for the treatment of open tibial fractures in sub-Saharan Africa. At a mean of 4 years after injury, fracture-related infection and nonunion became chronic conditions in nearly a quarter of the participants who experienced these complications, regardless of reintervention. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.